PENGARUH TINGKAT BUNGA DOMESTIK DAN LUAR NEGERI SERTA NILAI TUKAR MATA UANG RUPIAH TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Gulo, Marta K; Munthe, Kornel (Jurnal Manajemen dan Bisnis, 2013)
This study aimed to analyze the influence of the Domestic Interest Rate and Foreign Interest Rate and Foreign Exchange Rate Rupiah against the Composite Stock Price Index at the Indonesia Stock Exchange. Population which is the object of this study is the period of 1952-2012 the entire value of JCI. The sample used is the period of 2010-2012 the entire value JCI listed in Indonesia Stock Exchange. The data collected is secondary data with engineering documentation. The analytical method used is SEM (Structural Equation Modeling) which is operated through a program AMOS 22. From the analysis and discussion shows that the Domestic Interest Rate and Interest Rate Foreign Affairs has a significant effect on Exchange-exchange amount, partially negative effect Domestic Interest Rate Interest Rate Foreign and has a positive influence on Exchange-exchange amount. While the Exchange-exchange Rupiah positive effect on Composite Stock Price Index at the Indonesia Stock Exchange.